Lao People's Democratic Republic Systematic Country Diagnostic : Priorities for Ending Poverty and Boosting Shared Prosperity - World Bank Group (World Bank, Washington, DC, 2017)
Lao PDR has made important gains in development in recent decades. Incomes rose, poverty declined, access to several key public services improved, and Lao PDR met a number of its Millennium Development Goals (MDGs). Lao PDR’s asset endowments, geography, and economic and social legacies have intertwined to shape a development experience of strong growth, limited inclusion, and considerable risks to sustainability. This reflects relative abundance of natural resources; landlocked and small size, ethnically diverse but part of a rapidly growing region; and institutions that have not kept pace with the changes in the economy. This Systematic Country Authority Diagnostic (SCD) aims to identify interventions that would deliver sustained growth and edge Lao PDR toward the twin goals of ending extreme poverty and boosting shared prosperity. The SCD employs a framework with three main pathways toward the twin goals, each addressing weaknesses identified in the diagnostics. Sustainably and efficiently managing the country’s natural resources, including collecting and managing resource rents, (Pathway 1) is critical to delivering strong growth and securing resources to build Lao PDR’s endowments of human and physical capital. Pathway 2 focuses on unlocking opportunities in the non-resource sectors to increase farmers’ incomes and create non-farm jobs, while Pathway 3 emphasizes improvements in human capital required to increase the ability of people to take on these opportunities. Measures to address the high vulnerability of people in Lao PDR further inform Pathway 3. The SCD also highlights the importance of strengthening institutions and governance, a critical cross-cutting challenge that affects progress in each of the three areas above. The pathways can be easily mapped to the three main outcomes of the eighth National Socio-Economic Development Plan (NSEDP).